2021
DOI: 10.3390/molecules26113315
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclic Thioxanthene Derivatives: Studies on Fluorescence and Antitumor Activity

Abstract: Thioxanthones are bioisosteres of the naturally occurring xanthones. They have been described for multiple activities, including antitumor. As such, the synthesis of a library of thioxanthones was pursued, but unexpectedly, four tetracyclic thioxanthenes with a quinazoline–chromene scaffold were obtained. These compounds were studied for their human tumor cell growth inhibition activity, in the cell lines A375-C5, MCF-7 and NCI-H460. Photophysical studies were also performed. Two of the compounds displayed GI5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A remarkable increase in the intracellular fluorescence of cells exposed to compounds 10-13 and 15-17 was observed, making it impossible to assess the effect of these thioxanthone derivatives on P-gp expression. In fact, compounds 15-17 had previously been reported as fluorescent compounds [15] and this characteristic limited some of the studies reported herein. Only compounds 9 and 14 were tested further for their potential to modulate P-gp expression.…”
Section: Effects On P-gp Expression and Activitymentioning
confidence: 79%
See 2 more Smart Citations
“…A remarkable increase in the intracellular fluorescence of cells exposed to compounds 10-13 and 15-17 was observed, making it impossible to assess the effect of these thioxanthone derivatives on P-gp expression. In fact, compounds 15-17 had previously been reported as fluorescent compounds [15] and this characteristic limited some of the studies reported herein. Only compounds 9 and 14 were tested further for their potential to modulate P-gp expression.…”
Section: Effects On P-gp Expression and Activitymentioning
confidence: 79%
“…Four tetracyclic thioxanthenes (15-18, Table 1) were also synthesized under the same conditions as compounds 8-13. These were obtained from guanidine or urea derivatives leading to a quinazoline-thiochromene scaffold, as previously described [15]. material for the coupling with sulfamides, which were less reactive (procedure b).…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of xanthenes, especially thioxanthenes, has increased remarkably in recent years due to their wide range of biological and pharmacological properties. As an example of its biological and pharmacological properties, anticancer, antitumor, antiviral, antimicrobial, antibacterial, and anti-inflammatory activities can be cited. Moreover, some types are also used as materials in dye technology, , sensor, , and organic light-emitting diodes (OLEDs) due to the conjugation and heteroring in their structures, ensuring optical and electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%